Optical applications in metrology - Valera, Aníbal (1998)
A basic requirement of the actual modern Industry is its ability to work with precision machinery, specially in branches as: Metal-mechanics, electronic and construction. The goal has been to increase productivity and quality employing precision engineering. Metrology, the science of measurements, was the keystone of this development. In this article we present some local contributions in the optical Metrology. We describe laboratory equipment to measure : spectral optical response (Transmission, Absorption), thickness and displacement lenghts determinations.